Esophageal and Mediastinal Lesions Following Multielectrode Duty‐Cycled Radiofrequency Pulmonary Vein Isolation: Simple Equals Safe?. Issue 4 (21st January 2016) - ZELLERHOFF, STEPHAN; LENZE, FRANK; ULLERICH, HANSJÖRG; BITTNER, ALEX; WASMER, KRISTINA; KÖBE, JULIA; POTT, CHRISTIAN; ECKARDT, LARS; MÖNNIG, GEROLD
Abstract : Background: The development of esophageal lesions following atrial fibrillation (AF) ablation has frequently been reported. Mediastinal tissue layers and the posterior wall of the left atrium are in close proximity to the site of ablation. Hence, mucosal lesions might solely represent the "tip of the iceberg." We therefore investigated patients undergoing multielectrode phased radiofrequency (RF) ablation (PVAC®, Medtronic Inc., Minneapolis, MN, USA) for symptomatic AF by radial endosonography (EUS) in conjunction with conventional endoscopy esophago‐gastro‐duodenoscopy (EGD) to visualize potential mediastinal injuries following pulmonary vein isolation (PVI). Methods and Results: Eighteen patients (six women, mean age 52.8 ± 12.8 years, range 32–72 years) underwent PVI using multielectrode phased RF ablation and EGD and EUS following PVI within 48 hours. Postablation periesophageal lesions were detected by EUS in 10 out of 18 patients (56%). Four out of 10 lesions consisted of mild changes like small pericardial effusions, whereas six out of 10 patients had more severe lesions of the mediastinum, including one patient with changes of the esophageal mucosa. No atrio‐esophageal fistula developed during follow‐up (FU; mean FU 215 ± 105 days). Conclusions: Mediastinal and esophageal structural changes occurred in a substantial number of patients. These findings highlight the necessity of close FU and the awareness of the potential development of an atrio‐esophageal fistula also after multielectrode catheter ablation.